ANALYSIS OF SHORT RIGID CAISSONS WITH GRANULAR CORE FOR ALLUVIAL LOWLANDS - S. M. Ali Jawaid; Madhira R. R. Madhav (Lowland Technology International, 2003)
A new composite foundation is being proposed for foundations in saturated loose alluvial deposits. A simplified theoretical approach using linear Winkler type responses, is presented in this paper for the analysis of the proposed foundation. Extensive parametric studies in terms of load sharing and settlement reduction as functions of various parameters, e.g. length to diameter ratio and inner to outer diameter ratio of the caisson, Poission’s ratios of soil and granular core material, relative stiffnesses of core, shear and bearing stiffnesses, are presented to predict the response of the composite foundation.